Strategi Misi Lintas Budaya Berdasarkan 1 Korintus 9:19-23 - Yohanes Andi; Oktavina Tola; Yabes Doma; I Ketut Gede Suparta (Jurnal Teologi Kontekstual Indonesia, 2020)
Cross-cultural mission strategy based on 1 Corinthians 9: 19-23. There are several main problems, one of which is that 1 Corinthians 9: 19-23 has been studied by several researchers and interpreters, but they look at it from another side. And also in the service really needs a strategy especially in carrying out cross-cultural services. By using a qualitative method with literature study approach and using the Hermeneutic Bible method. To find the results of the cross-cultural mission strategy carried out by Paul. Based on the analysis of the text of 1 Corinthians 9: 19-23, the author found three mission strategies in cross-cultural namely not exclusive, not selfish and does not discriminate against people based on background or social status.